PENYELESAIAN SENGKETA ILEGAL FISHING DI WILAYAH LAUT NATUNA ANTARA INDONESIA DENGAN CHINA - Tiara Aji Damastuti; Rivinta Cahyu Hendrianti; Roro Oktavia Laras; Rahmawati Agustina (Jurnal Reformasi Hukum : Cogito Ergo Sum, 2018)
In order to the welfare of the Indonesian water territories, the government continues to protect the sea to avoid cases of illegal fishing. The case of illegal fishing going on in the Natuna territorial waters caused a lot of the negative impact for Indonesia. Various efforts have been made to handle the cases of illegal fishing whether conducted by foreign fishermen and fishermen. One of the cases illegal fishing by foreign ships and foreign fishermen who in the Natuna Sea by China. This study aims to analyze the efforts of the Indonesian Government in tackling illegal fishing in the territory of the Natuna Sea and the dispute settlement of cases of illegal fishing that especially happened in the Natuna. The procedure used this research in the collection of data and using the procedures that the normative. Protection of Indonesia's marine area to Illegal fishing has been set in article 9 of Law No.45 of 2009 on fisheries.